UNEMPLOYMENT, COMMERCIAL MOTORCYCLE AND CRIME IN NIGERIA - Kpae, Dr. Gbenemene (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Employment in Nigerian is pervasive and is further compound by the present economic recession in which many companies have downsized and increasing the number of unemployed. r millions of jobless and unskilled Nigerians. Driven by the hash economic climate many unemployed and unskilled Nigerians particularly youths have seen riding commercial motorcycle as a source of survival. Despite providing daily means for earning a living for many unemployed people, motorbikes have also become an instrument for committing crimes by many youths with high propensity for criminal behaviour. In many urban and rural areas where commercial motorcycles operate, motorbikes provide easy means for criminals to escape without police detection and apprehension. Many commercial motorcyclists have been involved in petty crimes such as hand bag and telephone snatching, and more dangerous crimes such as armed robbery, rapes, kidnapping and suicide bombing. This paper examines how unemployment propels jobless people into using commercial motorcycle to commit crime.